The role of free radicals in ethiopathogenesis of diseases - Gürkan, Hakan (İstanbul Kültür Üniversitesi, 2008)
Free radicals can be defined as atoms or molecules containing one or more unpaired electrons in their orbitals. Their formation occurs continuously in the cells as a consequence of both enzymatic and nonenzymatic reactions. It has been estimated that the average person has around 10000–20000 free radicals attacking each body cell each day. Some free radicals are good in that they enable your body to fight inflammation, kill bacteria, and control the tone of smooth muscles, which regulate the working of internal organs and blood vessels. On the other hand increased or uncontrolled free radical activity might combine with other factors to cause some diseases such as neurodegenerative diseases, heart disease, cancers etc. The balance between the production of free radicals and the antioxidant defences in the body has important health implications. Under the normal conditions the antioxidant defense system within the body can easily handle free radicals that are produced. If there are too many free radicals produced and too few antioxidants, this may cause chronic damage. The aim of this study is review the data on diseases which may be linked to free radicals in order to clarify the role of them in ethiopathogenesis of these diseases.
Keywords: Free radicals; biological effects; pathological effects; serbest radikaller; biyolojik etkiler; patolojik etkileri